Why do ants shift their foraging from extrafloral nectar to aphid honeydew?. Issue 5 (8th August 2013) - Katayama, Noboru; Hembry, David H.; Hojo, Masaru K.; Suzuki, Nobuhiko
Abstract: When aphids parasitize plants with extrafloral nectaries (EFNs) and aphid colony size is small, ants frequently use EFNs but hardly tend aphids. However, as the aphid colony size increases, ants stop using EFNs and strengthen their associations with aphids. Although the shift in ant behavior is important for determining the dynamics of the ant–plant–aphid interaction, it is not known why this shift occurs. Here, we test two hypotheses to explain the mechanism responsible for this behavioral shift: (1) Extrafloral nectar secretion changes in response to aphid herbivory, or (2) plants do not change extrafloral nectar secretion, but the total reward to ants from aphids will exceed that from EFNs above a certain aphid colony size. To judge which mechanism is plausible, we investigated secretion patterns of extrafloral nectar produced by plants with and without aphids, compared the amount of sugar supplied by EFNs and aphids, and examined whether extrafloral nectar or honeydew was more attractive to ants. Our results show that there was no inducible extrafloral secretion in response to aphid herbivory, but the sugar concentration in extrafloral nectar was higher than in honeydew, and more ant workers were attracted to an artificial extrafloral nectar solution than to an artificial aphid honeydew solution. These results indicate that extrafloral nectar is a more attractive reward than aphid honeydew per unit volume. However, even an aphid colony containing only two individuals can supply a greater reward to ants than EFNs. This suggests that the ant behavioral shift may be explained by the second hypothesis.